2015
DOI: 10.1136/vr.102751
|View full text |Cite
|
Sign up to set email alerts
|

Investigating common clinical presentations in first opinion small animal consultations using direct observation

Abstract: Understanding more about the clinical presentations encountered in veterinary practice is vital in directing research towards areas relevant to practitioners. The aim of this study was to describe all problems discussed during a convenience sample of consultations using a direct observation method. A data collection tool was used to gather data by direct observation during small animal consultations at eight sentinel practices. Data were recorded for all presenting and non-presenting specific health problems d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 11 publications
5
32
0
8
Order By: Relevance
“…There are limitations to the application of veterinary clinical records for epidemiological research that have been reported previously [67,68]. In addition to these, it is worth noting that a final specified biomedical diagnosis is not always reached, or potentially even required, for effective clinical management in the primary-care setting [69,70]. A subset of dogs in the overall UK dog population are unregistered with a veterinary practice.…”
Section: Discussionmentioning
confidence: 99%
“…There are limitations to the application of veterinary clinical records for epidemiological research that have been reported previously [67,68]. In addition to these, it is worth noting that a final specified biomedical diagnosis is not always reached, or potentially even required, for effective clinical management in the primary-care setting [69,70]. A subset of dogs in the overall UK dog population are unregistered with a veterinary practice.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Veterinarians in clinical practice benefit from the knowledge of the most common presenting complaints and diagnoses as it facilitates preparedness to manage the majority of cases seen on a daily basis. 4,5 New graduates are expected to possess certain attributes and competences upon graduation, such as a thorough understanding of current concepts and principles of small animal medicine as well as knowledge about common animal diseases and their treatments. 6 Determining the most frequently observed presenting complaints and diagnoses enables subsequent tailoring of veterinary curricula to prioritise the teaching of the most commonly observed conditions.…”
mentioning
confidence: 99%
“…6 Determining the most frequently observed presenting complaints and diagnoses enables subsequent tailoring of veterinary curricula to prioritise the teaching of the most commonly observed conditions. 5,7,8 Quantifying the frequency of presenting complaints and diagnoses can also guide future research to focus on the most commonly encountered disorders. 5,8,9 Previous studies aimed at determining the most common conditions presenting to small animal veterinarians have utilised a variety of methods, each subject to limitations.…”
mentioning
confidence: 99%
“…Ongoing data collection will provide sufficient big data to identify additional associations and risk factors; indeed, the UK VetCompass database has collected data on more than 6 million unique animals in over 470 participating practices (11). Clinical decision-making and identification of research priorities can also be supported by the system, such as ranking of differential diagnoses, vaccine recommendations, directing veterinary education and training, and investigating changes in disease prevalence (12, 13). …”
Section: Introductionmentioning
confidence: 99%